2001
DOI: 10.1163/15685590151092643
|View full text |Cite
|
Sign up to set email alerts
|

Detection of CD55 and/or CD59 deficient red cell populations in patients with aplastic anaemia, myelodysplastic syndromes and myeloproliferative disorders

Abstract: Paroxysmal nocturnal haemoglobinuria (PNH) is an acquired clonal stem cell disorder characterized by intravascular haemolysis, venous thrombosis, marrow hypoplasia, frequent episodes of infection, and rarely leukaemic conversion. At the cellular level, PNH is characterized by the decrease or absence of glycosylphosphatidylinositol (GPI)-anchored molecules, such as CD55 and CD59, from the cell surface. PNH-like clones have been described in various haematological disorders. The link between PNH and aplastic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
1
20
0
4
Order By: Relevance
“…4 Recently, several researchers reported that 15-88.6% of untreated and/or treated AA patients have GPIdeficient cells [5][6][7][8][9][10][11][12][13][14] as do 10-23% of MDS patients. 12,[15][16][17] The proportions of GPI-deficient cells in AA and MDS patients varied greatly (0.003-99%) and were usually lower than those in PNH patients. [5][6][7][8][9][10][11][12][13][14][15][16][17] In addition, PIG-A mutations have partially been reported in patients with AA, 11,18 AA/PNH, 3,19 and MDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, several researchers reported that 15-88.6% of untreated and/or treated AA patients have GPIdeficient cells [5][6][7][8][9][10][11][12][13][14] as do 10-23% of MDS patients. 12,[15][16][17] The proportions of GPI-deficient cells in AA and MDS patients varied greatly (0.003-99%) and were usually lower than those in PNH patients. [5][6][7][8][9][10][11][12][13][14][15][16][17] In addition, PIG-A mutations have partially been reported in patients with AA, 11,18 AA/PNH, 3,19 and MDS.…”
Section: Introductionmentioning
confidence: 99%
“…12,[15][16][17] The proportions of GPI-deficient cells in AA and MDS patients varied greatly (0.003-99%) and were usually lower than those in PNH patients. [5][6][7][8][9][10][11][12][13][14][15][16][17] In addition, PIG-A mutations have partially been reported in patients with AA, 11,18 AA/PNH, 3,19 and MDS. 15,17 However, it could not be ruled out that these AA and MDS patients analyzed for PIG-A gene abnormality are actually PNH, because the AA and MDS patients had 2.4-28.5% and 1.19-22% of GPI-negative erythrocytes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…To av pasientene med sykdommen var diagnostisert med kronisk myeloproliferativ sykdom (myelofibrose). Paroksysmal nattlig hemoglobinuri assosiert med kronisk myeloproliferativ sykdom er sjeldent, men det er beskrevet tidligere (17).…”
Section: Diskusjonunclassified
“…CD55 and CD59 deficiency has been studied in other diseases and correlated with its severity. [29][30][31][32][33][34][35][36] Yamaguchi et al 37 showed that 28.6% of the patients with aplastic anemia (AA) and 27.8% of the patients with myelodysplasia syndrome (MDS) presented a poor population of CD59 in erythrocytes. Wang et al 38 observed a significant CD55 and CD59 reduction in 52% of neutrophils in patients with AA not treated.…”
Section: C3 and C5 Convertasementioning
confidence: 99%